Species Diversity and Distribution Pattern of Grassland and Cultivated Land Species in Upper Manang, Nepal Trans-Himalayas - Bhatta, Kuber Prasad; Chaudhary, Ram Prasad (Scientific World, 2010)
One of the easiest and the most common way to estimate the biological diversity at a place is to enumerate the organisms at species level, which helps to find the basic patterns of biodiversity at the place. A sound knowledge on floristic composition of particular area is essential to understand the resources, their sustainable use and conservation purposes. Altogether 600 specimens were collected from the Upper Manang area covering an elevation gradient of 2600m to 5200m from sea level, and of which 220 species belonging to 138 genera and 50 families were identified up to species level and used to estimate species richness. Of the total identified species, greatest diversity was found within the families Compositae and Labiatae, comprising 14 and 11 genera, respectively. Similarly, the greatest species diversity was found within the genera Potentilla (12 species) and Primula (6 species). Second order polynomial regression showed unimodal pattern of species richness along elevation gradient, showing greatest species richness between 3500m to 4000m altitude, whereas no any angiosperm species was encountered beyond 5100m. Key words: Species diversity; Grassland; Cultivated land; Manang. DOI: 10.3126/sw.v7i7.3831 Scientific World Vol.7(7) 2009 pp.76-79